Activity-Based Anorexia Induces Browning of Adipose Tissue Independent of Hypothalamic AMPK - Fraga, Angela; Rial-Pensado, Eva; Nogueiras, Rubén; Fernø, Johan; Diéguez, Carlos; Gutierrez, Emilio; López, Miguel (Frontiers in Endocrinology, 2021)
Anorexia nervosa (AN) is an eating disorder leading to malnutrition and, ultimately, to energy wasting and cachexia. Rodents develop activity-based anorexia (ABA) when simultaneously exposed to a restricted feeding schedule and allowed free access to running wheels. These conditions lead to a life-threatening reduction in body weight, resembling AN in human patients. Here, we investigate the effect of ABA on whole body energy homeostasis at different housing temperatures. Our data show that ABA rats develop hyperactivity and hypophagia, which account for a massive body weight loss and muscle cachexia, as well as reduced uncoupling protein 1 (UCP1) expression in brown adipose tissue (BAT), but increased browning of white adipose tissue (WAT). Increased housing temperature reverses not only the hyperactivity and weight loss of animals exposed to the ABA model, but also hypothermia and loss of body and muscle mass. Notably, despite the major metabolic impact of ABA, none of the changes observed are associated to changes in key hypothalamic pathways modulating energy metabolism, such as AMP-activated protein kinase (AMPK) or endoplasmic reticulum (ER) stress. Overall, this evidence indicates that although temperature control may account for an improvement of AN, key hypothalamic pathways regulating thermogenesis, such as AMPK and ER stress, are unlikely involved in later stages of the pathophysiology of this devastating disease.